Efektivitas Cool Pack (Kompres Dingin) Terhadap Nyeri Saat Pemasangan Infus Pada Anak Di Rumah Sakit X - Suhartilah; Roza Indra Yeni; Maria Susila Sumartiningsih (Akademi Keperawatan Yarsi Samarinda, 2026)
Abstract Pain during IV insertion is a common experience for children and can cause anxiety, fear, and procedural trauma. Non-pharmacological interventions, such as the use of cool packs, are an effective strategy for reducing pain in pediatric patients. The purpose of this EBN was to analyze the effectiveness of cool packs in reducing pain in children during IV insertion at Royal X Hospital. Methods: This EBN used an experimental design with a pretest-posttest approach and a control group. The sample consisted of four preschool children undergoing IV insertion, divided into an intervention group and a control group. Pain levels were measured using cool packs before and after the cool pack intervention. Data were analyzed descriptively and bivariately using a comparison of means test. Results: Before the intervention, the average pain score in the intervention group was 1.41 (SD 0.401), higher than the control group's 1.00 (SD 0.000), with p = 0.020 (<0.05), indicating a significant difference. After the intervention, the majority of children in the intervention group experienced mild pain (75%), while 25% experienced moderate pain. No children experienced severe pain. These results indicate that administering a cool pack effectively reduced pain levels in children during IV insertion, although baseline pain levels differed slightly between groups. Conclusion: The cool pack intervention proved effective as a non-pharmacological strategy to reduce pain during IV insertion in children, thereby improving the comfort and procedural experience of pediatric patients.